1994
DOI: 10.3109/00498259409043234
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and biliary metabolites of pyrene in rainbow trout (Oncorhynchus mykiss)

Abstract: 1. Pyrene was administered i.p. as a single dose to trout (Oncorhynchus mykiss). Urine was collected continuously for 3 days and bile sampled at the end of this period. Pyrene metabolites in these biological fluids were identified by 1H-nmr spectrometry, glc-ms and hplc-ms. 2. 1-Hydroxypyrene was the major oxidation metabolite in the urine and bile. Small amounts of 1,6-dihydroxypyrene and a putative 1,8-dihydroxypyrene metabolite also were detected. Unchanged pyrene was not found in any of these biological fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Similarly, Law et al (1994) reported that l-hydroxypyrene was primarily conjugated with glucuronic acid or sulphate in the bile of rainbow trout (free 1-hydroxypyrene: 4.05k1.47 pglml; p-glucuronide: 779k270 ~g l m l ; sulphate: 270k49.4 pglml). In Varanasi et al (1 98l), metabolites in bile from two groups of starry flounder (4 and 12OC) at 24 and 168 hr after feeding were characterized by high percentages (>85%) of the conjugates, of which glucuronides were the major components.…”
Section: Pyrene Metabolismmentioning
confidence: 85%
See 3 more Smart Citations
“…Similarly, Law et al (1994) reported that l-hydroxypyrene was primarily conjugated with glucuronic acid or sulphate in the bile of rainbow trout (free 1-hydroxypyrene: 4.05k1.47 pglml; p-glucuronide: 779k270 ~g l m l ; sulphate: 270k49.4 pglml). In Varanasi et al (1 98l), metabolites in bile from two groups of starry flounder (4 and 12OC) at 24 and 168 hr after feeding were characterized by high percentages (>85%) of the conjugates, of which glucuronides were the major components.…”
Section: Pyrene Metabolismmentioning
confidence: 85%
“…Previous mammalian and microbial biotransformation studies have shown that the major oxidation metabolite of pyrene is I-hydroxypyrene, which may be metabolized further by conjugation reactions to form highly water-soluble metabolites (Law et al 1994;Pelletier et al 1997). Besides I-hydroxypyrene, small amounts of 1,6-dihydroxypyrene and 1,8-dihydroxypyrene were discovered as metabolites in the study conducted by Law et al (1994).…”
Section: Pyrene Metabolismmentioning
confidence: 96%
See 2 more Smart Citations
“…However, in rainbow trout, these metabolites accounted for only a trace amount of the total IBF ($1%), glucuronic conjugates being dominant (95-99%). Also, similar types of metabolites (hydroxides as well as glucuronide and sulfate conjugates) have been identified from the bile of rainbow trout exposed to, e.g., PAHs and resin acids [41,42].…”
Section: Concentrations Of Bile Metabolitesmentioning
confidence: 97%